Bioenzyme-based nanomedicines for enhanced cancer therapy - Ding, Mengbin (2022)
Bioenzymes that catalyze reactions within living systems show a great promise for cancer therapy, particularly when they are integrated with nanoparticles to improve their accumulation into tumor sites. Nanomedicines can deliver toxic bioenzymes into cancer cells to directly cause their death for cancer treatment. By modulating the tumor microenvironment, such as pH, glucose concentration, hypoxia, redox levels and heat shock protein expression, bioenzyme-based nanomedicines play crucial roles in improving the therapeutic efficacy of treatments. Moreover, bioenzyme-mediated degradation of the major components in tumor extracellular matrix greatly increases the penetration and retention of nanoparticles in deep tumors and infiltration of immune cells into tumor tissues, thus enhancing the efficacies of chemotherapy, phototherapy and immunotherapy. In this review, we summarize the recent progresses of bioenzyme-based nanomedicines for enhanced cancer therapy. The design and working mechanisms of the bioenzyme-based nanomedicines to achieve enhanced chemotherapy, photothermal therapy, photodynamic therapy, chemodynamic therapy, radiotherapy and immunotherapy are introduced in detail. At the end of this review, a conclusion and current challenges and perspectives in this field are given.